Implementation of computer assisted assessment: lessons from the literature - Gavin Sim; Phil Holifield; Martin Brown (Association for Learning Technology, 2004)
This paper draws attention to literature surrounding the subject of computer-assisted assessment (CAA). A brief overview of traditional methods of assessment is presented, highlighting areas of concern in existing techniques. CAA is then defined, and instances of its introduction in various educational spheres are identified, with the main focus of the paper concerning the implementation of CAA. Through referenced articles, evidence is offered to inform practitioners, and direct further research into CAA from a technological and pedagogical perspective. This includes issues relating to interoperability of questions, security, test construction and testing higher cognitive skills. The paper concludes by suggesting that an institutional strategy for CAA coupled with staff development in test construction for a CAA environment can increase the chances of successful implementation.